Improving Student Learning Ability Through Communicative Language Learning Approach - Gitit I.P Wacana; Ika Paramitha Lantu (J-SHMIC : Journal of English for Academic, 2020)
This study aims to find out how students' speaking skills are developed through the Communicative Language Teaching approach. The significance of this research is to provide information for readers, especially for Pamona people as native speakers of the language, about the tenses in the Pamona language. Researchers used the Communicative Language Teaching (CLT) theory by Richard and Rodgers to develop students' speaking skills. The results of this study indicate that the objectives of this study have been achieved. The ability to speak English students successfully developed through the application of communicative language teaching approaches, through learning that triggers students to speak actively in the classroom through conversations as an exercise. In the first cycle all students attend the test. The results of the test in the first cycle were 12 students failed (33.3%) and 24 students (66.7%) passed. Achievement of the average grade of the class is also still low with a score of 65.8 grades C. Researchers then reflect on the learning process in this first cycle to be applied in the second cycle. In the second cycle, all students attend the test. The results of this test were 33 students (91.6%) successfully passed the test and 3 students (8.4%) failed. From the explanation of the results of the second cycle above, it appears that in this cycle the completeness criteria for class has been reached, in which 80% of the total number of students must achieve grades A, B or C or a value of more than 65. Students succeed in developing their English speaking skills because supported by teaching approaches that trigger students to speak and practice the functions of the language being learned.